The non-normativity of the Global South and the normativity of the Global North: The languaging as the normativity of diversity. (August 2022) - Dovchin, Sender; Shinjee, Bolormaa
Abstract: Drawing on social media context such as Facebook of international students from the Global South – Mongolia – in Australia, this article indicates that the diversity of "languaging" practices of migrants who come to settle in Australia from the Global South are better understood from the perspective of the "normativity of diversity". The notion of "languaging" is vital in capturing the current complexity of mixed and hybrid language practices fundamentally produced by the amalgamation of linguistic and cultural resources intersecting with Global South and North social, cultural and political landscapes. However, these languaging practices in Australia are neither non-normal nor substandard linguistic productions as mostly imagined in the local monolingual ideology. Instead, languaging practices of the migrants from the Global South in Australia should be understood as part of the new settlers' normative daily linguistic practices that cut across both online and offline settings. Consequently, it is crucial for language educators and language policy-makers in Australia to reconsider migrants' linguistic diversity in globalisation through the eyes of the "normativity of diversity".